Teamwork and intra-firm wage dispersion among blue-collar workers - Uwe Jirjahn; Kornelius Kraft (Institute for the Study of Labor (IZA), 2008)
Using data on a sample of manufacturing establishments in Germany, we find that the use of self-managed teams is associated with increased intra-firm wage inequality between skilled and unskilled blue-collar workers. We also show that moderating factors play an important role. While teamwork interacts positively with employer-provided further training and a production technology of the most recent vintage, it interacts negatively with the age of the establishment and the coverage by a collective bargaining agreement.
Keywords: J30; 330; Wage inequality; skill-biased organizational change; training; technology; establishment age; collective bargaining; Industriearbeiter; Lohnstruktur; Qualifikation; Gruppenarbeit; Betriebliche Bildungsarbeit; Betriebszugehörigkeit; Tarifpolitik; Deutschland